The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.31638/ijprs.v7.i1.00001
|View full text |Cite
|
Sign up to set email alerts
|

UV Spectrophotometric Method Development and Validation for Determination of Cetilistat in API and in Pharmaceutical Dosage Form

Abstract: Simple, rapid, sensitive, precise and specific UV Spectrophotometric for the determination of cetilistat in API and pharmaceutical dosage form were developed and validated. In this method solutions of cetilistat were prepared in n-hexane. Cetilistat standard solution was scanned in the UV range (400-200nm) in a 1cm quartz cell in a double beam UV spectrophotometer. The standard solution of cetilistat showed maximum absorption at wavelength 320.0 nm. The method obeys Beer's law in the concentration range from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…One spectrophotometric (Kshirsagar et al, 2018) anda few liquid chromatographic methods (El-Shanawani, 1998;Pajchel & Tyski, 2002;Laviana, Fernandez, Bayod & Blanco, 2003;Ganesh et al, 2018) have been reported previously for the quantitative determination of sultamicillin in pharmaceutical dosage form. In the method of Kshirsagar et al 2018 absorbance measurements were made at 232 nm which is the absorption maximum of sultamicillin in methanol. For the assay of sultamicillin in pharmaceutical dosage forms, more selective analytical methods are required to avoid possible interferences of the excipients.…”
Section: Introductionmentioning
confidence: 99%
“…One spectrophotometric (Kshirsagar et al, 2018) anda few liquid chromatographic methods (El-Shanawani, 1998;Pajchel & Tyski, 2002;Laviana, Fernandez, Bayod & Blanco, 2003;Ganesh et al, 2018) have been reported previously for the quantitative determination of sultamicillin in pharmaceutical dosage form. In the method of Kshirsagar et al 2018 absorbance measurements were made at 232 nm which is the absorption maximum of sultamicillin in methanol. For the assay of sultamicillin in pharmaceutical dosage forms, more selective analytical methods are required to avoid possible interferences of the excipients.…”
Section: Introductionmentioning
confidence: 99%